Pengaruh Financial Attitude, Financial Socialization dan Financial Experience Terhadap Perilaku Manajemen Keuangan - Idelia, Rizka Afifa; Ahmad, Gatot Nazir; Siregar, Muhammad Edo Suryawan (Program Studi Administrasi Niaga STIA Said Perintah, 2023)
This study aimed to examine the effect of financial attitudes, financial socialization, financial literacy and financial experience on financial management behavior. This study uses respondents with individual criteria aged 20-30 years and worked in the Greater Jakarta area. Respondents were selected using non-probability sampling methods and purposive sampling techniques. The data collection method was carried out using an online survey. Data were analyzed using the exploratory factor analysis (EFA) method to test the validity and look at Cronbach's alpha value for the reliability test. The general method variance test is intended to measure the bias or error that is owned in this research test. The structural equation model (SEM) was used to test this study's hypothesis. The results showed that financial attitudes and financial literacy had a significant effect on financial management behavior, financial socialization had a significant effect on financial literacy and financial experience had no significant impact on financial management behavior.